Organizational Factors and Work-Life Balance among Policewomen in Sarawak: Emotion Based Coping Strategy as Mediator - Mazuin, Rosman; Surena, Sabil; Zaiton, Hassan; Mark, Kasa (Human Resource Management Academic Research Society (HRMARS), 2020)
Policing is an extremely demanding profession and woman have no choice for working hours which may lead to work-life imbalance. Thus using the suitable coping strategy is paramount to ensure work life balance. The purpose of this study is to examine the effect of emotion based coping strategy as mediator between the selected organizational factors (flexible working hour, organization support and self-management) on work life balance. A total of 110 policewomen in Kuching, Sarawak responded to the survey questionnaire. The finding shows that emotion based coping strategy mediate only the relationship between self- management and work life balance. Thus, in order to assist policewomen to experience WLB, the organization should encourage policewoman to learn to have some ‘me time” besides providing support such as counselling and mentoring